ChatGPT and other AI Users: Innovative and Creative Utilitarian Value and Mindset Shift (Journal of Namibian Studies : History Politics Culture, 2023)
With the advent of ChatGPT and other AI technologies, technology-based learners have gained access to a new tool that offers relief and support in their academic pursuits. ChatGPT, powered by OpenAI's language model, has the ability to generate ideas, provide information, and assist in various tasks. This research aims to explore the relief that ChatGPT provides to technology-based learners by examining its utilitarian value and its impact on enhancing innovative and creative skills. By understanding the benefits and limitations of ChatGPT, educators and learners can harness its potential to improve learning outcomes and navigate the challenges associated with AI integration in education.